2009
DOI: 10.1007/s11064-008-9902-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Excitatory Amino Acid Neurotransmitters on Blood–Brain Barrier Disruption in Focal Cerebral Ischemia

Abstract: This study was performed to determine whether exogenous N-methyl-D: -aspartate (NMDA) or alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) would aggravate blood-brain barrier (BBB) disruption in focal cerebral ischemia in rats. Forty-five minutes after middle cerebral artery (MCA) occlusion, one of the following patches was applied to the exposed ischemic cerebral cortex of each rat: normal saline (control), 10(-5) M AMPA, 10(-4) M AMPA, 10(-5) M NMDA, or 10(-4) M NMDA. At 1 h after MCA occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Abundant evidence demonstrated that BBB disruption induced by I/R injury contributes to vasogenic brain edema, aggravating the ischemic brain damage eventually (Chi et al, 2009;Gidday et al, 2005). Matrix metalloproteinases (MMPs), a family of proteolytic enzymes, were reported to degrade several important structural proteins in the microvascular wall, resulting in an increase of the microvascular permeability and BBB disruption (Gidday et al, 2005;Piao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant evidence demonstrated that BBB disruption induced by I/R injury contributes to vasogenic brain edema, aggravating the ischemic brain damage eventually (Chi et al, 2009;Gidday et al, 2005). Matrix metalloproteinases (MMPs), a family of proteolytic enzymes, were reported to degrade several important structural proteins in the microvascular wall, resulting in an increase of the microvascular permeability and BBB disruption (Gidday et al, 2005;Piao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant evidence demonstrates that cerebral ischemiainduced BBB disruption contributes to vasogenic brain edema and neutrophil infiltration, eventually aggravating the ischemic brain damage [5,6]. Matrix metalloproteinases (MMPs), a family of proteolytic enzymes, are reported to degrade important structures in the microvascular wall, resulting in an increase of the microvascular permeability and BBB disruption [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since BBB permeability plays a crucial role in determination of the extent of ischemic brain damage, factors that modify the susceptibility of BBB integrity can alter the overall outcome of ischemic stroke. Hyperglycemia significantly worsened BBB breakdown during ischemic condition, contributing to the aggravation of the consequences of stroke (57), and exogenous excitatory amino acid neurotransmitters disrupted BBB integrity during focal cerebral ischemia (58). Although the studies investigating the effect of heavy metals on BBB integrity are limited, several reports have given insights for heavy metalinduced BBB disruption (59).…”
Section: Role Of Bbb In Heavy Metal-associated Ischemic Brain Injurymentioning
confidence: 99%